2012
DOI: 10.3945/jn.111.140756
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms Upstream from the β-Carotene 15,15'-Monoxygenase Gene Influence Provitamin A Conversion Efficiency in Female Volunteers4

Abstract: β-Carotene, the most abundant provitamin A carotenoid in the diet, is converted to retinal by β-carotene 15,15'-monoxygenase (BCMO1). However, β-carotene absorption and conversion into retinal is extremely variable among individuals, with proportions of low responders to dietary β-carotene as high as 45%. Recently, 2 common nonsynonymous single nucleotide polymorphisms (SNPs) within the BCMO1 coding region (R267S; rs12934922 and A379V; rs7501331) revealed reduced catalytic activity, confirming that genetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 17 publications
5
101
1
Order By: Relevance
“…Rs4889286 or rs56389940, in composite LD with rs6564851 and in the same upstream area, was selected for the b-carotene, a-carotene, and lutein/zeaxanthin gene scores. SNPs upstream of BCMO1, rs7501331 + rs12934922, and rs7501331 alone were previously reported to reduce BCMO1 activity and were associated with fasting plasma b-carotene (7,9). Here, the rs12934922 T allele was positively associated with plasma b-carotene, and either rs12934922 or rs4889293, in composite LD with rs12934922, was selected for the provitamin A carotene gene scores.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rs4889286 or rs56389940, in composite LD with rs6564851 and in the same upstream area, was selected for the b-carotene, a-carotene, and lutein/zeaxanthin gene scores. SNPs upstream of BCMO1, rs7501331 + rs12934922, and rs7501331 alone were previously reported to reduce BCMO1 activity and were associated with fasting plasma b-carotene (7,9). Here, the rs12934922 T allele was positively associated with plasma b-carotene, and either rs12934922 or rs4889293, in composite LD with rs12934922, was selected for the provitamin A carotene gene scores.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, through a genome-wide association study (GWAS), Ferrucci et al (8) identified 4 other SNPs in modest (r 2 = 0.22-0.55) linkage disequilibrium (LD) with each other near BCMO1 that were related to circulating carotenoid concentrations. Specifically, rs6564851 was associated with increased band a-carotene and decreased lutein, zeaxanthin, and lycopene (8); rs6564851 was recently reported to reduce BCMO1 activity by 48% in females (9).…”
Section: Introductionmentioning
confidence: 98%
“…A large genome-wide association study identified a SNP about 7 kb upstream of the BCMO1 gene that strongly correlates (p ϭ 1.6 ϫ 10 Ϫ24 ) with increased fasting BC levels in serum (13). A small intervention study with female volunteers revealed that carriers of this SNP evidence a reduced BC conversion rate by about 50% (14). These observations could be explained by altered intestinal BCMO1 activity, an assumption supported by the finding that a rare missense mutation in human BCMO1 as well as genetic disruption of BCMO1 in mice lead to highly elevated BC blood levels and hypovitaminosis A (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide study has associated a single nucleotide polymorphism (SNP, rs6564851) 7-kb upstream of the BCMO1 gene with increased fasting BC serum levels (13). A small intervention study provided evidence that this SNP is associated with reduced intestinal BC conversion (14). Additionally, several lines of evidence indicate that conversion of BC is under negative feedback control of vitamin A (15)(16)(17).…”
mentioning
confidence: 99%
“…Polymorphisms in BCO1 are associated with elevated fasting b-carotene concentrations (42), and a lower conversion efficiency of b-carotene, albeit at pharmacologic doses (43). Although statistically significant, a polymorphism associated with a higher b-carotene concentration only explained 1.9% of the variance at the population level (42), and other variations in genes related to the absorption, transport, and cleavage of carotenoids are likely involved in the individual variation in response to dietary carotenoids (16) as well as their transcription factors (18).…”
Section: Inferences From Serum Carotenoids Consistent With High Livermentioning
confidence: 99%